Entry strategies in the face of incumbents dominant position: the case of advanced renewable energy technologies - Fontes, M. (2013)
The paper discusses the entry strategies adopted by research-based firms introducing advanced renewable energy technologies in the electricity production sector, which combines strong incumbent power with fast technological change. Drawing on contributions from the literatures on sustainability transitions and on strategic management of technology we build an analytical framework to address the conditions faced by the new entrants and the attitude of established incumbents towards their technologies. This framework is applied through in-depth case studies of new firms in two energy fields that display different levels of technological maturity: wind and wave energy. The paper presents preliminary results from a first set of case studies, which provide some insights into the “commercialisation environment” prevailing in those fields. They suggest that research-based firms tend to depend on the complementary assets possessed by incumbents, but have conditions to protect their technologies; and that the technology is relevant for (at least some) incumbents, which show interest on them, or are directly involved in their development/use. This is, in most cases, conducive to “cooperation” strategies, which assume different forms according to the stage of development of the technology and its proximity to incumbent competences and business models